Membrane Permeabilization by Thrombin-Induced Platelet Microbicidal Protein 1 Is Modulated by Transmembrane Voltage Polarity and Magnitude - Koo, Su-Pin (American Society for Microbiology, 1999)
Thrombin-induced platelet microbicidal protein 1 (tPMP-1) is a small, cationic peptide generated from rabbit platelets when they are exposed to thrombin in vitro. It has potent microbicidal activity against a broad spectrum of bacterial and fungal pathogens, including Staphylococcus aureus. Previous in vitro studies involving whole staphylococcal cells and planar lipid bilayers (as artificial bacterial membrane models) suggested that membrane permeabilization by tPMP-1 is voltage dependent (S.-P. Koo, M. R. Yeaman, and A. S. Bayer, Infect. Immun. 64:3758–3764, 1996; M. R. Yeaman, A. S. Bayer, S. P. Koo, W. Foss, and P. M. Sullam, J. Clin. Investig. 101:178–187, 1998). Thus, the aims of the present study were to specifically characterize the electrophysiological events associated with membrane permeabilization by tPMP-1 by using artificial planar lipid bilayer membranes. We assessed the influence of transmembrane voltage polarity and magnitude on the initiation and modulation of tPMP-1 membrane permeabilization at various concentrations of tPMP-1 (range, 1 to 100 ng/ml) added to the cis side of the membranes. The incidence of membrane permeabilization induced by tPMP-1 at all of the concentrations tested was more frequent at −90 mV than at +90 mV. It is noteworthy that membrane permeabilization due to 1-ng/ml tPMP-1 was successfully initiated at −90 mV but not at +90 mV. Further, the mean onset times of induction of tPMP-1 activity were comparable under the various conditions. Modulation of ongoing membrane permeabilization was dependent on voltage and tPMP-1 concentration. Membrane permeabilization at a low tPMP-1 concentration (1 ng/ml) was directly correlated with trans-negative voltages, while a higher tPMP-1 concentration (100 ng/ml) induced conductance which was more dependent on trans-positive voltages. Collectively, these data indicate that the mechanism of tPMP-1 microbicidal activity at the bacterial cytoplasmic membrane may involve distinct induction and propagation stages of membrane permeabilization which, in turn, are modulated by transmembrane potential, as well as peptide concentration.